2007
DOI: 10.1002/rcs.139
|View full text |Cite
|
Sign up to set email alerts
|

Advanced da Vinci surgical system simulator for surgeon training and operation planning

Abstract: Virtual reality is a useful technique for medical training. The simulator is currently in its early stages, but this preliminary work is promising.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…Proper ports placement and surgeon experience could decrease the incidence of arm collision-related error. 14,15 In our series, only one error (battery loss) resulted in delayed surgery. Surgical delay related to robotic failure has been examined by several other studies.…”
Section: Discussionmentioning
confidence: 64%
“…Proper ports placement and surgeon experience could decrease the incidence of arm collision-related error. 14,15 In our series, only one error (battery loss) resulted in delayed surgery. Surgical delay related to robotic failure has been examined by several other studies.…”
Section: Discussionmentioning
confidence: 64%
“…Other groups are working on the development of different VR simulators for robotic surgery and reported about their The Scientific World Journal prototypes [24,25]. There is one laparoscopic simulator which can be converted into a robotic simulator and can train basic robotic skills [26]; however, van der Meijden et al were not able to establish construct validity for this simulator and improvement is necessary before using it in robotic training programs [27].…”
Section: Discussionmentioning
confidence: 99%
“…The simulator reproduces the behaviour of the da Vinci system by implementing its kinematics and thus providing a promising tool for training and a way to plan operations. 164 Students of today easily and readily adopt virtual reality as part of their regular training program. 165 The new generation of medical students has grown up in the age of computer technology and it has been shown that prior videogame experience can shorten the time to learn basic skills in virtual reality simulation for minimal invasive surgery, 166 except for robotic suturing, where prior videogame experience had a negative impact on robotic performance.…”
Section: Training and Education In Roboticsmentioning
confidence: 99%